2016
DOI: 10.1007/s13277-016-5265-x
|View full text |Cite
|
Sign up to set email alerts
|

Violacein induces death of RAS-mutated metastatic melanoma by impairing autophagy process

Abstract: Treatment of metastatic melanoma still remains a challenge, since in advanced stage it is refractory to conventional treatments. Most patients with melanoma have either B-RAF or N-RAS mutations, and these oncogenes lead to activation of the RAS-RAF-MEK-ERK and AKT signal pathway, keeping active the proliferation and survival pathways in the cell. Therefore, the identification of small molecules that block metastatic cell proliferation and induce cell death is needed. Violacein, a pigment produced by Chromobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
10
0
4
Order By: Relevance
“…RAS-activating mutation increases autophagy, which enhances tumor growth, survival, and oncogenesis, and is associated with the development of some deadly cancers, including lung, colon, and pancreatic [ 82 , 83 , 84 , 85 ]. Some studies have revealed that a high level of autophagy is observed in RAS-activating mutated cells, and cell survival is dependent on autophagy during nutrient starvation [ 86 , 87 ]. In addition, inhibition of autophagy-related protein enhances the accumulation of damaged mitochondria and decreases cell growth [ 88 , 89 , 90 ].…”
Section: Autophagy As a Regulators Of Tumor Promotionmentioning
confidence: 99%
“…RAS-activating mutation increases autophagy, which enhances tumor growth, survival, and oncogenesis, and is associated with the development of some deadly cancers, including lung, colon, and pancreatic [ 82 , 83 , 84 , 85 ]. Some studies have revealed that a high level of autophagy is observed in RAS-activating mutated cells, and cell survival is dependent on autophagy during nutrient starvation [ 86 , 87 ]. In addition, inhibition of autophagy-related protein enhances the accumulation of damaged mitochondria and decreases cell growth [ 88 , 89 , 90 ].…”
Section: Autophagy As a Regulators Of Tumor Promotionmentioning
confidence: 99%
“…The production of violacein evolved as a defense for C. violaceum biofilms and phagocytosis of a single C. violaceum results in lysis, release of violacein, and induction of apoptosis in protozoa [ 45 ]. Additionally, violacein has been shown to be toxic not only to protozoa but also to induce apoptosis in a range of human cancer cell lines [ 46 , 47 , 48 , 49 , 50 ]. Furthermore, violacein is insoluble in water [ 51 ] and thus fits our model of identifying natural compounds that may or may not require specific solvents for mammalian cell assays.…”
Section: Resultsmentioning
confidence: 99%
“…On a more optimistic note, it is worth mentioning the attempts to use violacein to treat gastroenterological diseases, including malignancies, and well as other cancers, e.g. melanoma [12,13,14].…”
Section: Case Studymentioning
confidence: 99%